1978
DOI: 10.1111/j.1471-0528.1978.tb15820.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Platelet Function in Pre‐eclampsia

Abstract: Summary Platelet behaviour was studied in groups of women suffering from mild and severe pre‐eclampsia, and compared with normal pregnant and non‐pregnant controls. Platelets from women with severe pre‐eclampsia were less responsive than normal to a variety of aggregating agents, and this impairment was significant in response to collagen and vasopressin. Women with severe pre‐eclampsia had raised plasma adenine nucleotide levels and lowered platelet 5‐hydroxytryptamine levels compared with the controls. Plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…Increased sensitivity to aggregating agents in vitro has been described following myocardial infarction [93], in patients with diabetes mellitus [94], transient cerebral ischemia [95], cerebrovascular disease [96], hyper-fl-lipoproteinaemia [97], Raynaud's phenomenon [98], and hypertension [96,[99][100][101], suggesting a facilitation of release of platelet-bound mediators platelet-bound mediators in these conditions [5]. The actual occurrence of a platelet release processes in these clinical conditions is documented by the increase of platelet release markers, in particular betathromboglobulin [78,81] [110,111], by the elevation of thromboxane B 2, the stable degradation product of thromboxane A 2 formed from platelet membrane-bound arachidonic acid [5], in patients with myocardial ischemia [112-116[, by the diminished platelet 5-HT content in pre-eclampsia and hypertension [117][118] and the elevated plasma 5-hydroxyindoles in patients with myocardial infarction [79,119]. These observations strongly suggest [45] that platelet activation, sufficient to produce intravascular release of such mediators as 5-HT, occurs in some cardiovascular patients.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Increased sensitivity to aggregating agents in vitro has been described following myocardial infarction [93], in patients with diabetes mellitus [94], transient cerebral ischemia [95], cerebrovascular disease [96], hyper-fl-lipoproteinaemia [97], Raynaud's phenomenon [98], and hypertension [96,[99][100][101], suggesting a facilitation of release of platelet-bound mediators platelet-bound mediators in these conditions [5]. The actual occurrence of a platelet release processes in these clinical conditions is documented by the increase of platelet release markers, in particular betathromboglobulin [78,81] [110,111], by the elevation of thromboxane B 2, the stable degradation product of thromboxane A 2 formed from platelet membrane-bound arachidonic acid [5], in patients with myocardial ischemia [112-116[, by the diminished platelet 5-HT content in pre-eclampsia and hypertension [117][118] and the elevated plasma 5-hydroxyindoles in patients with myocardial infarction [79,119]. These observations strongly suggest [45] that platelet activation, sufficient to produce intravascular release of such mediators as 5-HT, occurs in some cardiovascular patients.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Some investigators reported an increase in in vitro plate let aggregability in the latter part of pregnancy [ 17], others found no significant difference between nonpregnant and pregnant women in the maximum rates of platelet aggre gation in response to collagen, adrenaline, ADP or arachidonic acid [14]. There are also data on diminished responsiveness of platelets to platelet activating factor and other aggregating agents during pregnancy [13,14], It is known that in the case of preeclampsia platelets that have undergone aggregation and disaggregation within the circulation, and which are being aggregated in the microcirculation of various organs, such as the placenta or kidneys, are hyperaggregable. and in uteroplacental arteries many of the same processes are found, similar to those seen in atherosclerosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have also found enhanced spontaneous platelet aggrega tion in myocardial infarction [2,3] atherosclerosis obliter ans [4] and in diabetes mellitus [5], Normal pregnancy is characterized not only by a 'hypercoagulable state' resulting in an increased susceptibil ity to thrombotic disturbances [6], but also by increased production of antiaggregating substances generated by uteroplacental tissues, such as prostacyclin [7], adenosine diphosphatase [8], vasoactive intestinal polypeptide [9], a factor from the placental brush border membrane with aggregation inhibition activity [10] and with prostacyclin activity protecting effect [11], There are remarkable dif ferences in platelet behavior and responsiveness to plate let-activating factors between patients with normal and complicated pregnancy and between nonpregnant and pregnant subjects [12,13]. The platelet-aggregating and -disaggregating properties, the platelet turnover, the coag ulation and fibrinolysis could be changed in different ways during pregnancy [ 14]. The aim of the present study was therefore to try and determine the summarized effect of aggregating and antiaggregating processes in circulating blood during pregnancy, applying the method of Wu and Hoak [1 ] with some modifications.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other investigators could not establish any differences between pregnant and nonpregnant women. 28,42 The recently reported increase in the plasma levels of thromboxane B2 and its release from thrombin-induced platelet aggregates in pregnant women suggests enhanced in vivo platelet activity during pregnancy. 43 In conclusion, the various changes in the hemostatic variables, especially the increase in clotting factor levels, in Saudi pregnant women are similar to many previously published results and support the description of pregnancy being a "hypercoagulable state" 2,44 that assures rapid and effective hemostasis during parturition.…”
Section: Discussionmentioning
confidence: 99%